A edição crítica das obras de João Penha (1839-1919): um monumento mais perene do que o bronze - Pereira, Elsa (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article briefly presents our PhD thesis in Romance Literatures and Cultures, defended in may 2013, at the Faculty of Arts, University of Porto (Portugal). By going through thousands of documents of different types, we were able to edit the complete works of João Penha (1839-1919), who was at the helm of Portuguese literature at the end of the 19th century. Based on a genetic critical approach, our edition aimed to integrate several levels of documentation, providing raw material to contextualize the author’s creation, thus enriching the wider context of the time